Alien invasive species: is the EU's strategy fit for purpose? - Davies, Peter G.G. (Edward Elgar, 2016)
An analysis is provided of the EU's 2014 Regulation on the Prevention and Management of the Introduction and Spread of Invasive Alien Species by primarily addressing the extent to which it complies with international guidance.